2005
DOI: 10.1080/09548980500300507
|View full text |Cite
|
Sign up to set email alerts
|

Fixational instability and natural image statistics: Implications for early visual representations

Abstract: Under natural vicv-.Ting-conditions 1 srnall movements of the eye: head, and body prevent the maintenance of a, steady direction of gaze. It is known tlu.tt stinmli tend to fade when they are stabilized on the retina for scveraJ seconds. Hm:vever: it is undcar whether the physiological motion of the retinal image serves a visual purpose during the brief periods of natural visual fixation. Thb r:;tucly exrtmines the in1paet of Hxational instability on the statistics of the visua.1 input to the retina. and on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 41 publications
1
27
0
1
Order By: Relevance
“…Similarly, increasing sensory drive as the animal matures could also desynchronize neuronal activity, because uncorrelated peripheral inputs could serve to weaken or disorganize spontaneously correlated activity patterns (Rucci and Casile, 2005). Plucking of whiskers from early neonatal stages weakens the angular tuning of barrel cortical neurons (Simons and Land, 1987) without disrupting the cytoarchitectural and histochemical development of the barrel field (Simons and Land, 1987; Akhtar and Land, 1991; Fox, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, increasing sensory drive as the animal matures could also desynchronize neuronal activity, because uncorrelated peripheral inputs could serve to weaken or disorganize spontaneously correlated activity patterns (Rucci and Casile, 2005). Plucking of whiskers from early neonatal stages weakens the angular tuning of barrel cortical neurons (Simons and Land, 1987) without disrupting the cytoarchitectural and histochemical development of the barrel field (Simons and Land, 1987; Akhtar and Land, 1991; Fox, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a general characterization of EyeRIS performance, this article has reported examples of experimental applications related to our own research on fixational instability (Rucci & Casile, 2005;Rucci & Desbordes, 2003). In this context, we have shown that EyeRIS produces image stabilization with quality comparable to that of a stimulus deflector coupled with a DPI eyetracker, a standard noninvasive method for eliminating retinal image motion.…”
Section: Discussionmentioning
confidence: 99%
“…However, these pioneering experiments also suffered from a number of technological and methodological limitations, which cast serious doubts on extrapolating their conclusions to more natural viewing conditions [17, 21, 22]. Furthermore, the proposal of an involvement of fixational eye movements in spatial perception has recently found new support from multiples sources, including neurophysiological [16, 23, 24] and behavioral investigations [22, 25, 26], statistical examinations of retinal input signals [27, 28], and theoretical analyses of the impact of a continually moving retinal input on neural responses [15, 17, 18, 29, 30]. …”
Section: The Unsteady Eyementioning
confidence: 99%